Colorectal cancer methods and protocols - Beaulieu, Jean-François ca. 20./21. Jh (Springer New York, 2018)
This volume explores the latest developments in the study of the mechanisms, diagnostics, screening methods, and therapeutics of colorectal cancer. The book's chapters are divided into three parts: the chapters in Part One examine techniques used to study the molecular mechanisms in colorectal cancer development and progression. Part Two focuses on the innovative tools used to diagnose and detect cancer lesions in the early stages of cancer. Finally, Part Three discusses recent advancements in treating colorectal tumors and identifying new therapeutic molecules for treatment. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and comprehensive, Colorectal Cancer: Methods and Protocols is a valuable resource for any scientist and researcher interested in this field of study
Keywords: Cancer research; Dickdarmkrebs; Aufsatzsammlung